How Intrinsic Motivation augments Innovation and Commitment? A Moderated Mediation Model of Employee’s Trust and Engagement - Khan , Muhammad Tasnim; Ali , Syed Ahmad; Rehman, Hafeez ur (Pakistan Journal of Humanities and Social Sciences, 2024)
Based on self-determination theory, the study aimed to gauge the impact of intrinsic motivation on employees’ engagement which later augments innovation and commitment. It further examined the moderating impact of employee’s trust on the relationship between motivation and engagement. The authors collected data through an online survey from 350 respondents from the telecommunications industry in Pakistan using a cross-sectional design through simple random sampling. For analysis, the SEM (structural equation modeling) technique was used to test direct and indirect effects. The results confirmed the initially hypothesized framework of a moderated mediation mechanism between intrinsic motivation, engagement, job innovation, and commitment. Mediation analysis reflects that employee’s engagement mediates between both intrinsic motivation and job innovation as well as with commitment. Further, employee’s trust was found to be positively moderating between intrinsic motivation and employee’s engagement. Unlike traditional approaches to test mediation between intrinsic motivation and commitment and job innovation, the study examines a moderated mediation mechanism of how employee’s intrinsic motivation spurs engagement in the presence of employee’s trust which can subsequently increase innovative behavior and commitment of the employee. The study explains the self-determination mechanism in the context of telecommunications industry in Pakistan. Theoretical and practical implications are also discussed.